BRIGHT LIGHT THERAPY IN SELECTED NEUROPSYCHIATRIC AND SLEEP-RELATED CONDITIONS: A NARRATIVE REVIEW - Hanna Maruchniak; Wiktoria Marzec; Paulina Biedroń; Anna Skrzypek; Maciej Hutkowski; Mikołaj Zbrożek; Zuzanna Chwostek; Bartłomiej Kosiarski; Patrycja Markowicz; Krzysztof Biłyk (International Journal of Innovative Technologies in Social Science, 2026)
Bright light therapy (BLT), defined as timed exposure to high-intensity light, is an established nonpharmacological treatment for seasonal affective disorder (SAD) and is increasingly being investigated in other areas of neuropsychiatry and sleep medicine. This narrative review synthesizes evidence published between 2015 and 2025 on the clinical applications of BLT in SAD, non-seasonal major depressive disorder, bipolar depression, shift-work-related circadian misalignment, sleep and selected non-motor symptoms of Parkinson’s disease. Relevant English-language literature was identified through PubMed and Google Scholar, with emphasis on systematic reviews, meta-analyses and randomized controlled trials. The strongest evidence supports BLT in winter-pattern SAD, where it remains first-line acute treatment associated with clinically meaningful symptom improvement. In non-seasonal major depressive disorder, pooled findings indicate a small-to-moderate antidepressant effect, although outcomes are more heterogeneous and seem to be influenced by treatment timing, chronotype and ambient light exposure. In bipolar depression, adjunctive BLT administered under mood-stabilizer coverage shows benefit and is generally well tolerated, with low short-term rates of manic or hypomanic switching when conservative protocols are used. In shift-work-related circadian disruption, BLT is associated with modest sleep benefits and measurable circadian phase delay, supporting its use as a strategy for circadian adaptation. In Parkinson’s disease, available studies suggest benefit for sleep disturbance and excessive daytime sleepiness, whereas effects on mood and other non-motor symptoms remain less consistent. Overall, BLT appears to be a clinically meaningful and feasible intervention across multiple conditions, although broader implementation is limited by protocol heterogeneity, biologically active control-light designs and limited long-term follow-up.